The Shadow Price of Aircraft Noise Nuisance - Bernard M.S. van Praag; B.E. Baarsma (Tinbergen Institute, 2000)
This paper has a twofold objective. First, we develop a new method toassess the monetary value for individuals of external effects (viz., aircraftnoise nuisance) which are not or only partly internalized in market prices. The method makes use of an ordinal index of life satisfaction as scored by individual respondents who are subjected in varying intensity to the external effect. Our second objective is to assess, with this method, to what extent noise nuisance effects around Amsterdam Airport Schiphol are internalizedand what should be the monetary compensation for the nuisance. Such acompensation scheme depends on, among other things, the objective noise level,income and the presence of noise insulation. The results are both significant and plausible. The method is generally applicable.
Keywords: 330; Opportunitätskosten; Lärm; Luftverkehr; Theorie; Amsterdam